Ottoman economic practices in periods of transformation - Fleet, Kate. (Ankara)
310 s.
Keywords: Financing the island of Crete / Kate Fleet -- The commerce of Crete / Kate Fleet -- The control of agricultural production in Crete / Kate Fleet -- From Crete to Bulgaria / Kate Fleet -- Economic transformations in the central Rumelian lands : an overview / Svetla Ianeva -- Manifestations and implications of early nineteenth-century transformations in the Ottoman fiscal system in the central Rumelian lands / Svetla Ianeva -- The tax payers' communities and the functioning of the fiscal system in nineteenth century Ottoman Rumeli / Svetla Ianeva -- Regulation and functioning of the Ottoman fiscal system in the 1860s and 1870s - evidence from the central Rumelian provinces / Svetla Ianeva.